2016
DOI: 10.1002/14651858.cd001001.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Lung volume reduction surgery for diffuse emphysema

Abstract: Lung volume reduction surgery for diffuse emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 159 publications
(17 reference statements)
0
37
0
Order By: Relevance
“…In all patients, FEV1 increased (+150 mL, +6.5%; P<0.001), RV decreased (−82 mL, −14.5%; P<0.001), 6MWD improved (+48 m; P<0.001), pO 2 increased (+12.6 mmHg; P<0.001) and quality of life improved as evidenced by change in SGRQ scores by −10.4 points (P<0.001). However, there was no significant improvement in pCO 2 or pulmonary arterial pressure. COPD exacerbation (41.4%), cough (41%) and pneumonia (17%) were the most frequent potential adverse events observed in patients, with Pseudomonas colonization noted in 8.1% of patients during the procedure.…”
Section: Coilsmentioning
confidence: 79%
See 1 more Smart Citation
“…In all patients, FEV1 increased (+150 mL, +6.5%; P<0.001), RV decreased (−82 mL, −14.5%; P<0.001), 6MWD improved (+48 m; P<0.001), pO 2 increased (+12.6 mmHg; P<0.001) and quality of life improved as evidenced by change in SGRQ scores by −10.4 points (P<0.001). However, there was no significant improvement in pCO 2 or pulmonary arterial pressure. COPD exacerbation (41.4%), cough (41%) and pneumonia (17%) were the most frequent potential adverse events observed in patients, with Pseudomonas colonization noted in 8.1% of patients during the procedure.…”
Section: Coilsmentioning
confidence: 79%
“…With advanced disease, response to treatment wanes and few options exist. Lung volume reduction surgery (LVRS) improves pulmonary function, exercise capacity and quality of life in a subset of patients, but due to perceived risks and costs is not commonly offered (2). Bronchoscopic lung volume reduction (BLVR) offers a possible alternative and much interest has been generated in the techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The question arises whether MIDs based on anchor techniques can be used across different interventions as several processes may underlie the observed effects of interventions . Possibly, MID determination in patients who undergo lung volume reduction surgery or other bronchoscopic treatment modalities such as lung volume reduction coils, airway sealants or thermal vapour ablation could provide different MID results . Further research is required to assess the influence of different bronchoscopic treatment options on the TLVR MID calculation.…”
Section: Discussionmentioning
confidence: 99%
“…22 A 2016 Cochrane review of 11 studies (1,760 participants), questioned the quality of the evidence but concluded that LVRS may lead to clinically meaningful benefits in lung function, exercise capacity, QoL and survival, especially in selected individuals with upper lobe predominant emphysema/lowbaseline exercise capacity. 23 The cost of the procedure has been predicted to fall considerably. At 5 years, the costeffectiveness of LVRS compared with SoC was $140,000 per quality-adjusted life-year (QALY) gained (95% confidence interval [CI]: $40,155-239,359), and was projected to be $54,000 per QALY gained at 10 years.…”
Section: Clinical Datamentioning
confidence: 99%